2008
DOI: 10.1248/jhs.54.589
|View full text |Cite
|
Sign up to set email alerts
|

Rhodomyrtone from Rhodomyrtus tomentosa (Aiton) Hassk. as a Natural Antibiotic for Staphylococcal Cutaneous Infections

Abstract: The ethanol extract of Rhodomyrtus tomentosa (Aiton) Hassk. (R. tomentosa) was determined for its antibacterial activity on staphylococci isolated from acne lesions. Antibiotic susceptibility patterns of the isolates were performed. Preliminary screening of the antibacterial property of the extract using disk diffusion method demonstrated pronounced antibacterial activity of the extract on all tested isolates. The average inhibition zones of 64 coagulase-positive and 85 coagulase-negative isolates were 12 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 26 publications
0
34
0
3
Order By: Relevance
“…However, the study challenges the use of rhodomyrtone as an alternative in treating cutaneous staphylococcal 12 infections [33]. The same study assessed the antibacterial activity of the crude ethanolic extract of R. tomentosa on staphylococci isolated from acne lesions, and the authors reported antibacterial activity against all isolated coagulase-positive and coagulase-negative staphylococci.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study challenges the use of rhodomyrtone as an alternative in treating cutaneous staphylococcal 12 infections [33]. The same study assessed the antibacterial activity of the crude ethanolic extract of R. tomentosa on staphylococci isolated from acne lesions, and the authors reported antibacterial activity against all isolated coagulase-positive and coagulase-negative staphylococci.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…[22] Taraxerol (32) [29] Trans-triacontyl-4-hydroxycinnamate (33) [26] 3,3',4,4'-tetra-O-methylflavellagic acid (34) [26] 3-O-(E)-coumaroyloleanolic acid (35) [26] (-)-(2R,3R)-1,4-O-diferuloylsecoisolariciresinol (36) [26] Arjunolic acid (37) [26] 4-hydroxy-3-methoxybenzoic acid (38) [26] Stigmast-4-en-3-one (39) [26] Oleanolic acid (40) [26] Methyl gallate (41) [26] 3-O-methylellagic acid 4-O-rhamnopyranoside (42) [26] …”
Section: Antifungal Activitymentioning
confidence: 99%
“…The ethanol was evaporated using a rotary evaporator and the extract was resuspended in 10 % DMSO (Merck) before use. Rhodomyrtone was isolated according to a method described previously and dissolved in 10 % DMSO (Saising et al, 2008). Vancomycin (Fluka) and DMSO were included as controls.…”
Section: Methodsmentioning
confidence: 99%
“…An ethanol extract of Rhodomyrtus tomentosa leaves as well as rhodomyrtone, a pure compound in the acylphloroglucinol class isolated from the leaves of this medicinal plant species, have shown profound antibacterial activity against a wide range of Gram-positive pathogenic bacteria with low MIC values, comparable to available antibiotics including vancomycin (Saising et al, 2008;Limsuwan et al, 2009;Voravuthikunchai et al, 2010). Natural compounds from certain plants such as carvacrol, thymol and salvipisone have also been demonstrated to exert effects on staphylococcal biofilm (Kuźma et al, 2007;Nostro et al, 2007;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The compound was isolated from Rhodomyrtus tomentosa (Aiton) Hassk. leaves and exhibits pronounced antibacterial activity against a wide range of Gram-positive bacteria (Limsuwan & Voravuthikunchai, 2008;Saising et al, 2008;Limsuwan et al, 2009a;Voravuthikunchai et al, 2010;Saising et al, 2011). The MIC and minimum bactericidal concentration values of rhodomyrtone against MRSA range from 0.39 to 0.78 mg ml 21 , which is very close to those of vancomycin (Limsuwan et al, 2009b).…”
Section: Introductionmentioning
confidence: 95%